Ethanol sensor based on Au-doped ZnO nanostructures - Auttasit Tubtimtae (2018)
Ethanol sensing characteristics of ethanol sensor based on Au-doped ZnO nanostructures were studied. Au-doped ZnO nanostructures with 5% gold by weight were prepared by thermal oxidation technique. The sintering time was varied for 6 hours and 24 hours. The wire-like or belt-like nanostructures with the sharp ends outward from microparticles were observed. The diameter and length of ZnO nanostructures are in the range of 250-750 nm and 1.7-7.0 μm, respectively, with the average diameter of 500 nm. EDS spectrum shows Au signal confirming incorporation of Au into ZnO nanostructures. For 24 hours sintering time, the diameter and length of ZnO nanostructures are 170-500 nm and 2.0-7.0 μm, respectively, with the average diameter of 330 nm. The average diameter for 24 hours sintering time is smaller than that of 6 hours sintering time. The response and recovery characteristics of Au-doped ZnO nanostructures upon exposure to ethanol concentration of 1000 ppm at different operating temperatures suggest that the sensitivity depend on operating temperatures. It is found that the highest sensitivity is 88 at 280 °C for 6 hours sintering time and about 170 at 300-320 °C for 24 hours sintering time. The longer sintering times the higher the sensitivity. The enhancement of sensitivity for longer sintering time may be explained in terms of the smaller size of nanostructures due to the increase of effective surface for absorption of ethanol on the surface. © 2007 IEEE.